B. Sometimes because in learned that it isn't always that way.
Answer:
(2x - 5 ) (3x^2 + 5x - 7) = 6x^3 - 5x^2 - 39x - 35
The product of 2x – 5 and 3x2 + 5x - 7equal to the product of 5x - 2 and 3x2 + 5x - 7 are not equal.
Step-by-step explanation:
Product means multiplication
Product of 2x - 5 and 3x^2 + 5x - 7
(2x - 5 ) (3x^2 + 5x - 7)
= 6x^3 + 10x^2 - 14x - 15x^2 - 25x - 35
Collect like terms
= 6x^3 + 10x^2 - 15x^2 - 14x - 25x - 35
= 6x^3 - 5x^2 - 39x - 35
Product of 5x - 2 and 3x^2 + 5x - 7
(5x - 2) (3x^2 + 5x - 7)
= 15x^3 + 25x^2 - 35x - 6x^2 - 10x + 14
Collect like terms
= 15x^3 + 25x^2 - 6x^2 - 35x - 10x + 14
= 15x^3 + 19x^2 - 45x + 14
The product of 2x – 5 and 3x^2 + 5x - 7equal to the product of 5x - 2 and 3x^2 + 5x - 7 are not equal.
They both consist of different variables in their multiplier
Answer:
7x -4= -28
Step-by-step explanation:
Answer:
x=12, y= 20
Step-by-step explanation:
We can find x using the pythagorean thereom because ABD is a right triangle.(D is the point between segments with legnth 5 and 11)
AC^2 + CD^2 = AD^2
x^2 + 5^2 = 13^2
x^2 = 25 = 169
x^2 = 144
x = 12
We may now find y using the pythagorean thereom because ABC is a right triangle. Right now we know x = 12
AC^2 + CB ^2 = AB^2
12^2 + 16^2 = y^2
144 + 256 = y^2
y^2 = 400
y= 20
<em>I hope this helps! :)</em>